Impact of the Snakes and Ladders Educational Game on Students’ Engagement in Learning - Fauziahnur, Fauziahnur; Baidullah, Baidullah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Mathematics learning interest at the primary level is widely recognized as a key determinant of students’ long-term achievement and attitudes toward the subject, making its early development an urgent educational priority. This study addresses the low level of mathematics learning interest among fourth-grade students at SD Negeri 7 Kuala Batee. An initial survey indicated that limited enthusiasm for mathematics hindered students’ understanding of basic concepts, largely due to monotonous teaching methods with minimal student engagement. To overcome this issue, the Snakes and Ladders game was introduced as a learning medium, grounded in constructivist theory and prior findings on play-based learning. Employing a quantitative approach with a pre-experimental one-group pretest–posttest design, the study involved 12 students. A Likert-scale questionnaire on learning interest, tested for validity and reliability, was used as the instrument. Results revealed an increase in mean scores from 72.50 to 82.42, with a paired-sample t-test showing significance at 0.000 (<0.05). Student interest categories also improved, with four students achieving the “very high” level and eight in the “high” category after the intervention. Despite limitations related to the absence of a control group and small sample size, the findings suggest the potential of game-based approaches to foster engagement in mathematics learning. This study contributes novelty by empirically demonstrating the effectiveness of Snakes and Ladders as a culturally relevant, low-cost, and interactive medium to enhance primary students’ interest in mathematics.